PP.18 Caesarean Section and Time to Next Birth, Ectopic Pregnancy, Miscarriage or Stillbirth-A Danish Register-Based Study. (26th April 2013) - O'Neill, SM; Agerbo, E; Kenny, LC; Henriksen, TB; Kearney, PM; Greene, RA; Mortensen, PB; Lutomski, JE; Khashan, AS; Meaney, S
Abstract : Aim: Estimate time to next birth, risk of miscarriage, ectopic pregnancy or stillbirth in women with primary Caesareans. Methods: Danish population-registry cohort of births from 1982–2010 (n = 833, 162). Analysis using Cox-regression models. Results: Prior Caesarean group had longer birth intervals. No increased risk of ectopic pregnancy or miscarriage, but significantly increased risk of stillbirth among women with a prior Caesarean. Conclusion: Prior Caesareans were associated with an increased birth interval and increased risk of stillbirth compared to vaginal deliveries.